2014
DOI: 10.1093/mnras/stu2134
|View full text |Cite
|
Sign up to set email alerts
|

X-ray variability of SS 433: effects of the supercritical accretion disc

Abstract: We study a stochastic variability of SS 433 in the 10 −4 − 5 × 10 −2 Hz frequency range based on RXTE data, and on simultaneous observations with RXTE and optical telescopes. We find that the cross-correlation functions and power spectra depends drastically on the precession phase of the supercritical accretion disc. When the wind funnel of the disc is maximally open to the observer, a flat part emerges in the power spectrum; a break is observed at the frequency 1.7 × 10 −3 Hz, with a power-law index β ≈ 1.67 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 23 publications
3
19
0
1
Order By: Relevance
“…The inferred emission region for this extended component is ∼ 10 12 − 10 13 cm (Marshall et al 2012;Kubota et al 2010;Krivosheyev et al 2009;Cherepashchuk et al 2007;Kotani et al 1996), which is as large or larger than the size of the accretion disk (Rout ≈ 2 × 10 12 cm: Gies et al 2002). The observed X-ray luminosity of SS 433 (LX ≈ 10 36 erg s −1 ) is ∼10 −3 -10 −4 times the true luminosity (Khabibullin & Sazonov 2016;Fabrika et al 2015;Medvedev & Fabrika 2010), because only a small fraction of X-rays are scattered at all angles by the outflow while most of the radiation is emitted inside the polar-axis funnel (Atapin et al 2015;Medvedev & Fabrika 2010). If a similar fraction of the X-ray luminosity is scattered by a wind above the disk plane in HLX-1, the pressure exerted by the irradiation flux would satisfy the condition given in Phillips & Podsiadlowski (2002) and cause an intermittent mass transfer.…”
Section: A Mass Transfer Instability Scenario For the Small Disk Casementioning
confidence: 95%
“…The inferred emission region for this extended component is ∼ 10 12 − 10 13 cm (Marshall et al 2012;Kubota et al 2010;Krivosheyev et al 2009;Cherepashchuk et al 2007;Kotani et al 1996), which is as large or larger than the size of the accretion disk (Rout ≈ 2 × 10 12 cm: Gies et al 2002). The observed X-ray luminosity of SS 433 (LX ≈ 10 36 erg s −1 ) is ∼10 −3 -10 −4 times the true luminosity (Khabibullin & Sazonov 2016;Fabrika et al 2015;Medvedev & Fabrika 2010), because only a small fraction of X-rays are scattered at all angles by the outflow while most of the radiation is emitted inside the polar-axis funnel (Atapin et al 2015;Medvedev & Fabrika 2010). If a similar fraction of the X-ray luminosity is scattered by a wind above the disk plane in HLX-1, the pressure exerted by the irradiation flux would satisfy the condition given in Phillips & Podsiadlowski (2002) and cause an intermittent mass transfer.…”
Section: A Mass Transfer Instability Scenario For the Small Disk Casementioning
confidence: 95%
“…Examining the fast X-ray variability of SS 433 (Revnivtsev et al 2006), it has been found that its power density spectrum is well-fitted by a broken power-law with a flat component (P ∝ f 0 ) below 10 −3 Hz (Atapin et al 2015;Atapin & Fabrika 2016). This type of variability is similar to the flat-topped noise (hereafter FTN) observed in BHBs at the state of low accretion rate, i.e.…”
Section: Introductionmentioning
confidence: 54%
“…The linear rms-flux relation is observed in binary systems with black holes and neutron stars (Uttley & McHardy 2001;Gleissner et al 2004;Uttley 2004), active galactic nuclei (Vaughan et al 2003b gests that this mechanism must work in these systems as well. Moreover, the Lyubarskii's model was successfully applied to the variability of the supercritical accretion disc of SS 433 (Revnivtsev et al 2006;Atapin et al 2015;Atapin & Fabrika 2016).…”
Section: Lyubarskii's Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing the RXTE observations of SS 433, we detected this break in the X-ray range (Atapin et al, 2015). In addition, we found the shape of the power spectrum and the presence of a break to depend on the precession phase: the break appears when the funnel is turned toward the observer.…”
Section: Introductionmentioning
confidence: 77%